Whole-organ analysis of TGF-β-mediated remodelling of the tumour microenvironment by tissue clearing - Shimpei I. Kubota (Nature Portfolio, 2021)
Shimpei Kubota et al. describe a pipeline for quantitative whole-organ analysis that that combines tissue clearing, 3D imaging, and machine learning for analysis of the tumour microenvironment. The authors apply this in a mouse model of lung tumour and reveal the role of TGF-β in remodelling the cellular microenvironment favouring metastatic invasion.